2016
DOI: 10.1097/ftd.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sulfamethoxazole Therapeutic Drug Monitoring to Clinical Efficacy and Toxicity

Abstract: Sulfamethoxazole serum levels outside the target range were not associated with increased rates of clinical failure in patients treated with TMP/SMX. There was also no association found between peak SMX levels and rates of adverse events. Although this study cannot disprove that dose adjustments after the initial SMX peak level may have affected clinical outcomes, the results suggest that the utility of SMX TDM may be limited to a subset of patients and requires further prospective investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Regarding the treatment of PJP, a multicenter retrospective study in Japan showed that a lower dose of TMP/SMX was as effective as higher doses of the same drug in patients with rheumatic diseases but was associated with fewer severe side effects. The role of therapeutic drug monitoring of TMP/SMX to reduce toxicity is still controversial 75,76 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the treatment of PJP, a multicenter retrospective study in Japan showed that a lower dose of TMP/SMX was as effective as higher doses of the same drug in patients with rheumatic diseases but was associated with fewer severe side effects. The role of therapeutic drug monitoring of TMP/SMX to reduce toxicity is still controversial 75,76 …”
Section: Resultsmentioning
confidence: 99%
“…Sulfonamides and trimethoprim display concentration dependent killing (AUC/MIC) and should be administered after dialysis, when administered intravenously. TDM of sulfamethoxazole and its main metabolite may be considered, especially in dialysis patients who are treated for Pneumocystis jiroveci pneumonia (PJP) with high doses of co-trimoxazole [43]. …”
Section: Pharmacokinetics and Pharmacodynamics Of Anti-infective Agenmentioning
confidence: 99%
“…Hence, the decision for prophylaxis should be individualized and the benefits of administering prophylaxis should always be balanced against the risks . Trimethoprim/sulfamethoxazole, the recommended agent for anti‐ Pneumocystis prophylaxis, is not without adverse events including myelosuppression, renal impairment, hyperkalemia, transaminitis, and hyperbilirubinemia . Furthermore, allergic reactions and additional pill burden can also contribute to morbidity.…”
Section: Discussionmentioning
confidence: 99%